The Vietnam Provincial Competitiveness Index 2007 Measuring Economic Governance For Private Sector Development - Edmund Malesky; Natasha Hanshaw; Janice Stallard; Tran Huu Huynh; Dau Anh Tuan; Do Le Thu Ngoc; Ton Nhat Quang; Le Thu Hien; Edmund Malesky; Natasha Hanshaw; Janice Stallard; Tran Huu Huynh; et al. (2007)
The PCI 2007 is the result of a major, on-going collaborative effort between the Vietnam Chamber of Commerce and Industry (VCCI) and the USAID-funded Vietnam Competitiveness Initiative (VNCI) Project, with a substantial contribution by VNCI-partner The Asia Foundation (TAF).